Role of impression cytology in diagnosis of ocular surface neoplasia - Napaporn Tananuvat (2018)
PURPOSE: To compare the accuracy of impression cytology in the diagnosis of ocular surface neoplasia with tissue histology. METHODS: We reviewed the histories of patients diagnosed with ocular surface neoplasia at the Chiang Mai University Hospital. All patients underwent both impression cytology and tissue biopsy. We compared the results of both methods. RESULTS: There were 55 patients (33 men and 22 women), with an age range of 12-99 years (mean, 51 years). Twenty patients had lesions in the right eye and 35 had them in the left eye. The most common histologic report was conjunctival-corneal intraepithelial neoplasia (38.2%), followed by squamous cell carcinoma (34.5%), nonneoplastic changes of squamous epithelia (10.9%), squamous papilloma (7.3%), conjunctival nevi (7.3%), and malignant melanoma (1.8%). Compared with histologic findings, the positive and negative predictive accuracy of impression cytology was 97.4% and 52.9%, respectively. For squamous neoplasms, squamous cell carcinoma had the highest correlation with histology. The presence of dysplastic cells suggested malignancy. CONCLUSIONS: This study shows that impression cytology might have a promising role in diagnosing ocular surface neoplasia for its high positive predictive accuracy compared with tissue histology. However, a fair negative predictive accuracy indicates that impression cytology is a valuable screening technique, but it is not a "gold standard." © 2008 Lippincott Williams & Wilkins, Inc.